Pengembangan Media Puzzle untuk Meningkatkan Kemampuan Membaca dalam Pembelajaran Tematik Siswa Kelas 1 Sekolah Dasar - Gunarti, Yustina; Ngatmini, Ngatmini; Asropah, Asropah (Universitas PGRI Semarang, 2023)
Thematic learning as a teaching and learning approach that involves several subjects in one theme to provide meaningful experiences for students.That thematic learning requires teachers who are creative both in choosing competencies from various lessons and arranging them so that learning becomes more meaningful, interesting, fun and Reading is a process carried out and used by readers to get messages, what the writer wants to convey through the medium of words or written language. This type of research is research and development (Research and Development or RD). it is necessary to design the development model used in this research is the Research Development model. This research was conducted in class I SD. The themes presented in the Puzzle learning media were all themes and it was necessary to include KI and KD in the Puzzle learning media that would be developed. The results of the study show that questions can be a tool to clarify students' understanding of the ideas contained in the reading, by providing questions students can remember and be aware of important facts or ideas contained in the reading. Development of puzzle media so as to improve reading skills in thematic learning of first grade elementary school students. Results of testing puzzle media products to improve reading skills in thematic learning of first grade elementary school students. These results explain that the reading ability of grade 1 elementary school students can be improved by using the development of puzzle media.